Online Education in Thailand During the Crisis and Beyond - Lipipun, Vichaya; Angasinha, Asisst. Prof. Dr. Chatwarun (Journal of Dhamma for Life, 2023)
Education has been slow in keeping up with other social changes in the digital era where all activities are performed online through mobile devices. Open-source resources, student-centered approach, and personalized learning are core elements of online education. A design to teach in the new digital ecology requires an extensive effort to ensure an engaging learning experience. This study aims to explain current trends in education transformation particularly during the COVID-19 pandemic, and beyond and provide recommendations to properly design participatory learning sessions. The study is an analysis of literature reviews that depicts the current situations of Thai education. The findings revealed that the digital infrastructure in Thailand particularly at schools is ready for the digital education transformation. Students should be able to utilize school resources to access free open-source materials online to supplement their learning. Regardless of the individuals’ proficiency in technology, digital literacy can be taught and learned to enable educators and learners to become active digital citizens who can self-taught through available resources online. With such capability of a digital citizen, lifelong learning become a vital aspect of life in a digital environment.